View of the west-facing elevation of the Neelkanth Mahadev Temple - Temples of India Project Team (Jio Institute, 2024)
This is a distant view of the west-facing elevation of the Neelkanth Mahadev Temple. Now inside a fencing boundary installed by the Archaeological Survey of India (ASI), the tri-kuta (triple-shrine) temple is surrounded by trees and agricultural fields. In the foreground, some architectural elements are scattered that must have been part of the Neelkanth Temple or other temples from the group.